2010
DOI: 10.1186/1471-2474-11-123
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA profiling in ischemic injury of the gracilis muscle in rats

Abstract: BackgroundTo profile the expression of microRNAs (miRNAs) and their potential target genes in the gracilis muscles following ischemic injury in rats by monitoring miRNA and mRNA expression on a genome-wide basis.MethodsFollowing 4 h of ischemia and subsequent reperfusion for 4 h of the gracilis muscles, the specimens were analyzed with an Agilent rat miRNA array to detect the expressed miRNAs in the experimental muscles compared to those from the sham-operated controls. Their expressions were subsequently quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…37 Several miRNAs were differentially regulated in hippocampi following global ischemia 38 and gracilis muscles in ischemic injury. 39 Yin et al showed that IPC in the heart resulted in upregulated miR-1, miR-21, and miR-24 expression. 23 Abundance of miR-23a, miR-326, miR-346, and miR-370 was altered in hepatic IPC.…”
Section: Discussionmentioning
confidence: 99%
“…37 Several miRNAs were differentially regulated in hippocampi following global ischemia 38 and gracilis muscles in ischemic injury. 39 Yin et al showed that IPC in the heart resulted in upregulated miR-1, miR-21, and miR-24 expression. 23 Abundance of miR-23a, miR-326, miR-346, and miR-370 was altered in hepatic IPC.…”
Section: Discussionmentioning
confidence: 99%
“…Although the pathophysiology of I/R injuries has not been fully elucidated due to complex interactions of inflammatory and immunologic signaling pathways [8], it is clear that accumulated free radicals and anaerobic metabolites during ischemia cause the migration of white blood cells and the release of inflammatory factors such as interleukin and free radicals in the reperfusion phase [9-13]. These compounds eventually damage muscle tissues, resulting in irrecoverable muscle damage and general complications [14-16].…”
Section: Introductionmentioning
confidence: 99%
“…In how far miRNAs are involved in IRI remains largely unclear: While first studies suggest a potential modulatory function of these small RNAs, reporting both aggravating as well as protective effects [16,19,53], other studies argue against an important pathophysiological role of miRNAs in IRI and ischemic postconditioning in larger mammals [3].…”
mentioning
confidence: 97%